Gambaran Faktor-Faktor yang Mempengaruhi dalam Pemakaian APD pada Pekerja di Balai Yasa Manggarai PT. KAI - Mutiara Kanza; Fitria Prihatini (STIKes Persada Husada Indonesia, 2020)
Hazard control by using PPE will not be maximized if the workers themselves do not use it, even though the company has provided it. The number of work accidents and occupational diseases in Indonesia is still quite high. One of the reasons is the low awareness of employers and employees about the importance of implementing OHS, one of which is the use of PPE. The use of PPE is the final stage in hazard control. The purpose of this study in general is to find out the description of the factors that influence the use of PPE for workers at Balai Yasa Manggarai PT. KAI. This type of research is a qualitative research with the focus of this research directed at the factors that influence the behavior of the use of PPE. The research was conducted at the Bogi Balai Yasa Manggarai unit, the Special Capital Region of Jakarta. The time of the research was carried out from May to August 2018. The research was conducted by involving six informants. Data were collected by means of interviews, document review and observation. The sampling method used in this research is purposive sampling. Data analysis carried out by triangulation technique. The study found that workers' knowledge of PPE was quite good, but there were still workers who were less disciplined by not wanting to wear PPE. The PPE facilities have been fulfilled, but there are still some PPE that are not yet available properly. Instructions for the use of PPE have been carried out properly and clearly, but there are still undisciplined workers who do not support the use of PPE when working. Workers stated that they had not received education related to K3 directly but only through slogans in the workplace, also only socialization from management. Some workers often do not use PPE when working on the grounds that it is hot, hot and uncomfortable wearing PPE. Others stated that they always wear PPE when working.